Titanium allergy: A literature review - Manish Goutam; Chandu Giriyapura; Sunil Kumar Mishra; Siddharth Gupta (Wolters Kluwer Medknow Publications, 2014)
Titanium has gained immense popularity and has successfully established itself as the material of choice for dental implants. In both medical and dental fields, titanium and its alloys have demonstrated success as biomedical devices. Owing to its high resistance to corrosion in a physiological environment and the excellent biocompatibility that gives it a passive, stable oxide film, titanium is considered the material of choice for intraosseous use. There are certain studies which show titanium as an allergen but the resources to diagnose titanium sensivity are very limited. Attention is needed towards the development of new and precise method for early diagnosis of titanium allergy and also to find out the alternative biomaterial which can be used in place of titanium. A review of available articles from the Medline and PubMed database was done to find literature available regarding titanium allergy, its diagnosis and new alternative material for titanium.